2008
DOI: 10.1002/jhet.5570450507
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and efficient method for synthesis of pyrimido[1,2‐a]‐benzimidazole derivatives under microwave irradiation

Abstract: A rapid and efficient method for synthesis pyrimido[1,2‐a]benzimidazole derivatives from readily available starting materials is accomplished under microwave irradiation. This method has the advantages of short reaction time, operational simplicity, increased safety for small‐scale high‐speed synthesis, and minimal environment impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…3 Analogs of this tricyclic system were synthesized by three component coupling under microwave irradiation and by using thiamine hydrochloride as a catalyst in aqueous conditions. [4][5][6][7] Attempts have been made in recent years to address the problem of discrimination of two regioisomeric products in the reactions of 2-aminobenzimidazoles, the origin which lies in the competing nucleophilicities of the 2-amino group and the ring nitrogen. 7 The variation on the active methylene component with ketoesters in ionic liquid medium has been reported and Sheibani et al demonstrated the multicomponent reaction of 2-aminobenzimidazole with ethyl-acyanocinnamoates in the presence of various base catalyst and the outcome of the product is differ from the present endeavor.…”
Section: Introductionmentioning
confidence: 99%
“…3 Analogs of this tricyclic system were synthesized by three component coupling under microwave irradiation and by using thiamine hydrochloride as a catalyst in aqueous conditions. [4][5][6][7] Attempts have been made in recent years to address the problem of discrimination of two regioisomeric products in the reactions of 2-aminobenzimidazoles, the origin which lies in the competing nucleophilicities of the 2-amino group and the ring nitrogen. 7 The variation on the active methylene component with ketoesters in ionic liquid medium has been reported and Sheibani et al demonstrated the multicomponent reaction of 2-aminobenzimidazole with ethyl-acyanocinnamoates in the presence of various base catalyst and the outcome of the product is differ from the present endeavor.…”
Section: Introductionmentioning
confidence: 99%
“…Shaaban 10 synthesised pyrimido [1,2a]benzimidazoles by the reaction of E-1-(1-methylbenzimidazol-2-yl)-3-(N,N-dimethylamino)prop-2-enone and 2-aminobenzimidazole in refluxing absolute ethanol catalysed by piperidine. Zhuang 11 developed a rapid and efficient method for the synthesis of pyrimido [1,2-a]benzimidazole derivatives under microwave irradiation. These approaches usually require forcing conditions, long reaction times, complex synthetic pathways and often, in organic solvents, the need for a catalyst.…”
mentioning
confidence: 99%